Networking of research institutes in Poland as a method of strengthening open innovation: Genesis and initial effects in the area of commercialization - Izabela Jonek-Kowalska (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The main objective of the research was to identify the synergistic effects in the area of commercialization of the networking of research institutes in Poland following a radical reform of the functioning of the national innovation system. This goal was pursued using the example of the Łukasiewicz Research Network, which brings together some of Poland's existing research institutes under the four pillars of the modern economy: (1) smart and clean mobility, (2) digital transformation, (3) health, and (4) sustainable economy and energy. Thus, the article attempts to answer the following research questions: What were the circumstances behind the networking of Polish research institutes, how did this networking take place, and what results in the area of commercialization have been achieved so far? The research conducted in this article showed that the institutes affiliated with the "digital transformation" group achieved the following successes in the first integration phase: (1) an increase in the share of revenue from the commercialization of research results as a basis for assessing the effectiveness of the use of scientific and research potential for strengthening innovation (in five of the six institutes researched) and (2) an increase in sales revenue (in three of the six institutes).
Keywords: 650; effects of networking research institutions; innovativeness in Poland; networking of research institutes; strengthening open innovation